Review and contribution to the stonefly (Insecta: Plecoptera) fauna of Azerbaijan - Murányi, Dávid; Manko, Peter; Kovács, Tibor; Vinçon, Gilles; Žiak, Matej; Kerimova, Ilhama G.; Snegovaya, Nataly Yurievna; Oboňa, Jozef (Zootaxa, 2021)
Known Plecoptera data published from Azerbaijan are critically reviewed. New records of 28 species are enumerated on the basis of specimens collected between 2017 and 2019, among them 16 are new for the fauna of Azerbaijan. Nemoura irani Aubert, 1964 is new for the whole Caucasian region, Leuctra sanainica Zhiltzova, 1960 and Plesioperla sakartvella (Zhiltzova, 1956) are new for the Greater Caucasus. The female and larva of an unknown Protonemura Kempny, 1898 species, collected in the Talysh Mts, are illustrated and described under temporary name Protonemura sp. AZE-1. A new species of Protonemura, collected both in the Azerbaijan and Georgian areas of the Greater Caucasus, will be formally described in a further paper. A male Protonemura specimen was found to be infected by mermithid worms, morphological lesions are illustrated and commented; this is the second documented case of mermithid infection in stoneflies. Subspecies level identity of Azerbaijani populations of Leuctra fusca (Linnaeus, 1758) proved to be problematic, morphological characters of the specimens are illustrated. Synonymy of Isoperla caucasica Balinsky, 1950 and I. pulchra Balinsky, 1950 under I. bithynica (Kempny, 1908) is disputed, the two names are combined under I. grammatica (Poda, 1761) sensu lato.